Diagnostic accuracy of glycoproteins in the assessment of liver fibrosis: A comparison between laminin, fibronectin, and hyaluronic acid - Younesi, Simin; Parsian, Hadi (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Liver fibrosis is a chronic liver injury affecting numerous individuals in the world, and efforts have been exercised for introducing a non-invasive method to evaluate the stages of liver fibrosis, which can be used instead of invasive methods, such as a liver biopsy. Various glycoproteins have been suggested by many investigators as indicators of liver fibrosis. This study aimed to compare the diagnostic accuracy of serum laminin, fibronectin, and hyaluronic acid levels in the assessment of liver fibrosis for discriminating patients from healthy subjects. Materials and Methods: We searched the English language literature to identify relevant studies regarding the role of glycoproteins in the assessment of liver fibrosis, using the following electronic databases: Medline, PubMed central, web of knowledge (ISI), Scopus, Google scholar, Springer, and Science Direct from 1981 to 2016. The key words used for searching were “glycoproteins”, “laminin”, “hyaluronic acid”, “fibronectin”, “diagnostic accuracy”, “assessment”, “liver fibrosis”, “cirrhosis”, “liver biopsy”, “grading”, and “staging”. The statistical data relevant for the diagnostic accuracy were extracted and analyzed using the summary receiver operating characteristic curves. Results: The diagnostic accuracy among the glycoproteins involved in this study were compared, and the area under curves for serum levels of laminin, hyaluronic acid, and fibronectin, as indicators of diagnostic accuracy, were 0.89, 0.82, and 0.73, respectively. Conclusion: It can be concluded that when liver biopsy is contraindicated, the serum levels of laminin, hyaluronic acid, and fibronectin can be considered screening tests as well as additional clinically useful tools for the evaluation of liver fibrosis. Cite this article as: Younesi S, Parsian H. Diagnostic accuracy of glycoproteins in the assessment of liver fibrosis: A comparison between laminin, fibronectin, and hyaluronic acid. Turk J Gastroenterol 2019; 30(6): 524-31.